Examination of student’s mathematical literacy in solving PISA questions on space and shape content in terms of metacognitive awareness - Erlina Maf'atun Rohmah; Nila Ubaidah (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Students that possess mathematical literacy are better able to identify, use, and interpret to solve difficulties in their daily lives. Students' mathematical literacy still needs to be improved, particularly in the areas of space and shape, according to the findings of the PISA survey conducted in Indonesia and observations made at SMA Negeri 10 Semarang. Metacognitive awareness, or students' capacity to successfully plan, monitor, and assess their problem-solving techniques, is one element that contributes to the development of mathematical literacy. Nevertheless, in the context of Indonesian mathematical literacy, this component is still hardly ever thoroughly examined. The purpose of this study is to explore students' mathematical literacy as they work with space-related PISA questions and shape content while taking into account their degree of metacognitive awareness. A descriptive qualitative methodology is employed, and data is gathered via expert-validated questionnaires, mathematics literacy assessments, and interviews. Reducing data, presenting data, and writing conclusions are all steps in the data analysis process.26 students from class X-3 at SMA Negeri 10 Semarang served as the study's subjects. They were divided into three groups low, medium, and high according to the answers to the metacognitive awareness questionnaire. The findings demonstrated that 15.38% of students with low metacognitive awareness could only complete one mathematical literacy test, which is problem formulation. Two indicators creating problems and employing concepts were met by students with moderate metacognitive awareness (65.38%). Formulating, employing, and understanding mathematical concepts were the three markers that students with high metacognitive awareness (19.23%) were able to meet simultaneously. This study confirms the importance of metacognitive awareness in improving mathematical literacy.